Gunshot residue and airbags: Part II. A case study. Issue 1 (2nd January 2019) - Laflèche, Denis J.N.; Hearns, Nigel G.R.
Abstract: We report a case of a shooting incident where analysis of airbag residue was of critical importance to interpret the forensic significance of gunshot residue (GSR) found on a suspect. The suspect had allegedly fired a gun at the victim after having been involved in a motor vehicle collision. Airbags in the suspect's vehicle had deployed during the collision, potentially exposing the suspect to a non-firearm source of GSR-similar particles. Samples collected from the interior of the deployed airbags were analyzed using scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM-EDS) and no particles similar to particles characteristic of GSR were found, eliminating the airbags as a potential source of GSR found on the suspect.